Comparative Analysis of Stock Valuation Models in Indonesian Shipping Companies - Dede Yusuf Maulana; Dharnita Chandra; Muhammad Muhammad (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study comparatively examines the effectiveness of three widely used stock valuation models in explaining the stock prices of shipping companies listed on the Indonesian Stock Exchange, with the aim of providing insights into their applicability and relevance in the context of the Indonesian market. Methodology: This study employed a quantitative research design using secondary panel data from Indonesian listed shipping companies from 2018 to 2023. Results: The findings indicate that although the Earnings-Based Model (EBO) and Price-to-Earnings (P/E) models showed partial significance with limited explanatory power, the P/S model demonstrated the strongest and most consistent influence on stock prices. Conclusions: Although the EBO model showed an extremely high Adjusted R², it indicated unrealistic overvaluation, while the P/E model had limited explanatory power. Overall, the P/S model is the most appropriate and representative model for valuing Indonesian shipping stocks. Limitations: This research is limited to shipping companies listed in Indonesia during the 2018–2023 period and relies solely on quantitative secondary data, which may not capture broader macroeconomic or industry-specific external factors. Contributions: This study enriches the capital market literature by providing sector-specific empirical evidence of the comparative performance of valuation models in an asset-intensive and cyclical industry.